Fluid replacement strategy during a 27-Km trail run in hot and humid conditions - Baillot, M.; Le Bris, S.; Hue, O. (International Journal of Sports Medicine, 2014)
We evaluated the effects of the fluid replacement strategy on core temperature, heart rate and urine osmolality during a 27-km trail run in tropical climate. 20 well-trained runners completed a 27-km trail race in tropical conditions. They were acclimatized to these conditions. Heart rate was monitored every 5 s, while core temperature and perceived thermal and comfort sensations were recorded before, at the 11th km, and just after the end of the race. Water intake, urine osmolality and body mass were measured before and after the race. Core temperature and the scores of perceived thermal and comfort sensations were significantly higher at the 11th km and at the end of the race compared to before the race, but not at the 11th km compared to the end of the race. No participant exhibited dehydration as assessed by urine osmolality. The less the trail runners weighed, the greater the heat retention was. The less hot they felt at the end of the race, the more they lost water, and the better the performance was. The fastest runners were able to tolerate a greater variation in core temperature between the beginning and the end of the trail race with lower water intake.